The lifestyle segmentation of house buyers’ in Malaysian new residential market - Fanny Foo , Suan Suan; Mohd Shafiei, Mohd Wira; Said, Ilias (2008)

(untitled)
The property development industry is in need of a comprehensive market intelligence to be able to predict and satisfy the needs of house buyers. Many developers based their marketing decisions on hunches and guesses, rather than on intelligence drawn from marketing research. Property developers can provide a better product offering to the house buyers if they know what the buyers want. But developers found it impossible to stick to a single strategy in approaching their customers, the main reason being, the residential property market consists of various segments. All too often development projects have been undertaken on the basis of superficial knowledge of the market. Most real estate purchases are considered high involvement goods that required complex decision making. Greater knowledge of real estate consumers and their behaviour will lead to better understanding and prediction of decision-makers’ actions in the real estate market. As a result, property developers must apply different sets of marketing strategies for different group of house buyers to ensure that they could successfully communicate with each specific segment separately. A lifestyle segmentation research could shed some light into the different segments of house buyers in the country. Each of these segments can then be profiled and characterised to give a more accurate picture of the behaviour and purchasing decisions of house buyers. In view of these statements, this paper attempts to broadly define lifestyle concepts based on the theories of lifestyle and consumer behaviour theories followed by discussion on the definition and structure of marketing and segmentation, i.e. types, segmentation scheme, benefit and advantages for residential market. This paper will also look into house buyers’ consideration such as model of consumer behaviour, consumer buying behaviour, the factor affecting the consumer buying process, consumer buying decision process and the type of consumer buying behaviour. The paper then concludes with a general view on the residential market scenario in Malaysia.